2017
DOI: 10.1063/1.5003326
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced transformations of indole and 3-formylindole monomers isolated in low-temperature matrices

Abstract: Photochemical transformations were studied for monomers of indole and 3-formylindole isolated in low-temperature noble-gas matrices. Upon UV (λ > 270 nm) irradiation of indole trapped in argon and neon matrices, the initial 1H-form of the compound converted into the 3H-tautomer. Alongside this photoinduced hydrogen-atom transfer, an indolyl radical was also generated by photodetachment of the hydrogen atom from the N1-H bond. Excitation of 3-formylindole isolated in an argon matrix with UV (λ > 335 nm) light l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…Indole and 3-formylindole differ by the formyl group bonded to C3 in the pentagonal ring (see Figure c). The latter compound has both 1 H - trans and 1 H - cis isomers, which are detectable, and may influence the shape and peak positions of the measured photoabsorption spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indole and 3-formylindole differ by the formyl group bonded to C3 in the pentagonal ring (see Figure c). The latter compound has both 1 H - trans and 1 H - cis isomers, which are detectable, and may influence the shape and peak positions of the measured photoabsorption spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The calculations of C, N, and O K-edge NEXAFS spectra were carried out with the Amsterdam Density Functional (ADF) program. , The TP-DFT ,− was employed with the generalized gradient approximation (GGA) PW86x Perdew and hybrid B3LYP xc potentials, while TDDFT calculations in the linear-response regime used both B3LYP and the range-separated hybrid CAM-B3LYP exchange-correlation (xc) potentials . In the case of 3-formylindole, all calculations were performed for its more stable 1 H - trans isomer …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the photoinduced structural transformations of indole, 7-azaindole, and 3-formylindole isolated in cryogenic noble-gas matrices were studied by Nowak and co-workers. , It was found that the tendency of indole and other indole derivatives to undergo hydrogen-atom transfer from N1 to C3 seems to be strongly related with the formation of C3-centered radicals, which facilitate the reattachment of the labile hydrogen atom at this position. The authors have observed that the pattern of photochemical transformations found for 7-AI isolated in solid n -H 2 and irradiated with UV (λ > 270 nm) light, is significantly different from that observed for the compound trapped in solid Ar.…”
Section: Introductionmentioning
confidence: 99%